'You Should See Yourself' : Jewish Identity in Postmodern American Culture - Brook, Vincent, 1946- (Book collections on Project MUSE., 2006)
The past few decades have seen a remarkable surge in Jewish influences on American culture. Entertainers and artists such as Jerry Seinfeld, Adam Sandler, Allegra Goodman, and Tony Kushner have heralded new waves of television, film, literature, and theater; a major klezmer revival is under way; bagels are now as commonplace as pizza; and kabbalah has become as cool as crystals. Does this broad range of cultural expression accurately reflect what it means to be Jewish in America today?. Bringing together fourteen new essays by leading scholars, You Should See Yourself examines the fluctuating.